Microwave Radar Sensing of Sea Waves: An Effective Reflection Coefficient - Karaev Vladimir; Panfilova Mariya Andreevna; Titchenko Yu.; Meshkov Evgeniy Mihaylovich; Kovaldov Dmitry; Xiuzhong Li; Yijun He (Russian Journal of Earth Sciences)
At the small incidence angles, the dominant backscattering mechanism for sea waves is the quasi-specular backscattering mechanism. The power of the reflected signal depends on the distribution function of the slopes of large-scale waves (in comparison with radar wavelength) and on the effective reflection coefficient, which is introduced instead of the Fresnel coefficient. In this paper, we discussed a new method for calculating the effective reflection coefficient from the wave scatterometer SWIM data. For the first time, measurements are performed by a radar at different azimuth angles at small incidence angles. This makes it possible to measure the effective reflection coefficient. An original algorithm was developed for data processing and determination of the total mean square slopes of large-scale sea waves and the azimuth dependence of the backscattering radar cross section at zero incidence angle. In the result of subsequent processing, the azimuth dependence of the effective reflection coefficient is retrieved. SWIM data were used to evaluate the developed algorithm. Processing of the test data set confirmed the efficiency of the algorithm. The azimuth anisotropy coefficients for the mean square slopes of large-scale waves and the effective reflection coefficient are calculated